2020
DOI: 10.1080/09593985.2019.1709233
|View full text |Cite
|
Sign up to set email alerts
|

Personalized community-based prehabilitation for a high-risk surgical patient opting for pylorus-preserving pancreaticoduodenectomy: a case report

Abstract: Introduction: Prehabilitation aims for an optimal physical functioning level before, during, and after hospitalization for major surgery. The purpose of this case report was to illustrate the care pathway of a high-risk patient who opted for pylorus-preserving pancreaticoduodenectomy, including preparation for this procedure by participating in a community-based exercise prehabilitation program. The report describes patient examination, evaluation in decision-making for surgery, the prehabilitation program, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Postoperative length of hospital stay tended to be shorter in the prehabilitation group compared to the usual care group (mean ± SD of 8 ± 8 versus 13 ± 20 days; P ¼ 0.078) [76]. Likewise, the case study of van Beijsterveld et al [77] reported that four weeks of supervised community-based prehabilitation (aerobic, resistance, and functional exercises) in a high-risk 75-year-old patient opting for pylorus-preserving pancreaticoduodenectomy improved preoperative physical fitness and resulted in an uncomplicated postoperative course. The preoperative period thus provides a window of opportunity for older patients undergoing elective HPB surgery, especially for those classified as high-risk patients, to decrease the risk of adverse postoperative outcomes by optimizing reserve capacity before surgery.…”
Section: Prehabilitation In Hepatopancreatobiliary Surgery: Current Ementioning
confidence: 82%
“…Postoperative length of hospital stay tended to be shorter in the prehabilitation group compared to the usual care group (mean ± SD of 8 ± 8 versus 13 ± 20 days; P ¼ 0.078) [76]. Likewise, the case study of van Beijsterveld et al [77] reported that four weeks of supervised community-based prehabilitation (aerobic, resistance, and functional exercises) in a high-risk 75-year-old patient opting for pylorus-preserving pancreaticoduodenectomy improved preoperative physical fitness and resulted in an uncomplicated postoperative course. The preoperative period thus provides a window of opportunity for older patients undergoing elective HPB surgery, especially for those classified as high-risk patients, to decrease the risk of adverse postoperative outcomes by optimizing reserve capacity before surgery.…”
Section: Prehabilitation In Hepatopancreatobiliary Surgery: Current Ementioning
confidence: 82%
“…The physiotherapeutic assessment of NS is based on the study of Berkel, et Borg RPE 13-15 in the high-intensity intervals or show no progress in their modified SRT performance at three weeks, the training intensity will be increased, taking into account patients' experiences and preferences 15 . In this way, the concept of titration is applied to make an individually tailored intervention to avoid non-response to the intervention 49…”
Section: Declarationsmentioning
confidence: 99%
“…Prehabilitation, as a new preoperative management concept proposed on the basis of ERAS, refers to the intervention means that patients receive cardiopulmonary function exercise mainly composed of aerobic exercise and resistance exercise, nutritional support mainly supplemented with whey protein, and psychological support before surgery [4] [5]. The aim is to alleviate the physical and mental stress of patients during perioperative period and optimize the surgical effect by means of a series of optimization measures [6].…”
Section: Introductionmentioning
confidence: 99%